2012
DOI: 10.1128/jvi.00796-12
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Immunodeficiency Virus Infection May Increase with Vaccine-Induced Immune Response

Abstract: e To explore the efficacy of novel complementary prime-boost immunization regimens in a nonhuman primate model for HIV infection, rhesus monkeys primed by different DNA vaccines were boosted with virus-like particles (VLP) and then challenged by repeated low-dose rectal exposure to simian immunodeficiency virus (SIV). Characteristic of the cellular immune response after the VLP booster immunization were high numbers of SIV-specific, gamma interferon-secreting cells after stimulation with inactivated SIV partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 26 publications
(30 reference statements)
1
39
1
Order By: Relevance
“…On one hand, they are intimately associated with protection through the provision of T-cell help for antibody production (34) and possibly direct cytolytic activity (9,25,(107)(108)(109). On the other hand, as predicted by Staprans et al (46) and confirmed elsewhere (97,98) in nonhuman primate studies, they can attenuate protection and lead to increased acquisition. The problem is now in focus, but its solution is intimately connected with the solution of antibody persistence.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 81%
See 1 more Smart Citation
“…On one hand, they are intimately associated with protection through the provision of T-cell help for antibody production (34) and possibly direct cytolytic activity (9,25,(107)(108)(109). On the other hand, as predicted by Staprans et al (46) and confirmed elsewhere (97,98) in nonhuman primate studies, they can attenuate protection and lead to increased acquisition. The problem is now in focus, but its solution is intimately connected with the solution of antibody persistence.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 81%
“…However, post hoc studies in nonhuman primates designed to model preexisting Ad5 immunity recapitulated the Step and Phambili trial results (97). Thus, nonhuman primate studies clearly show the possibility that vaccination can increase infection (46,97,98). The fact that the signal was missed in the nonhuman primate studies supporting the Step and Phambili trials (94,95,99) was more indicative of a problem with the study design than with the animal model itself because those studies did not take into account the possibility that preexisting Ad5 immunity could increase infection.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 99%
“…Again, the similarities in Gag-specific CD4 + T cell responses of mice and human vaccinees suggest that the ISH approach may be applicable to humans, as well. Whether this approach can be extended to Th cells with non-HIV specificities needs to be explored, but the idea to avoid possibly detrimental HIV-1-specific CD4 + T cell responses is appealing (58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…The tonsillar spray immunization with rAdV was carried out as described previously (34). From weeks 32 to 98 all of the group E animals (animals 13916, 13928, 13931, 13932, and 13935) were also immunized with unrelated simian immunodeficiency virus (SIV) an-tigens through DNA and viruslike particle vaccines as reported previously (31,35). Viral challenge.…”
Section: Methodsmentioning
confidence: 99%
“…Given the striking systemic and mucosal cellular and humoral immune responses induced by the DNA prime-tonsillar booster immunization (group E), we decided to extend the study in order to explore the protective efficacy of this immunization regimen. Due to other research commitments, the animals of group E were first included in an immunogenicity study with unrelated SIV antigens between weeks 60 and 84 (35). At 32 weeks after the last SIV immunization, corresponding to 126 weeks after the first RSV-F DNA immunization and 98 weeks after the last tonsillar booster immunization with the RSV-F adenoviral vector, RSV-F specific antibodies were still detectable in the blood and the BAL fluid (Fig.…”
Section: Mucosal Immune Responsesmentioning
confidence: 99%